Mechanisms of Mutagenic DNA Nucleobase Damages and Their Chemical and Enzymatic Repairs Investigated by Quantum Chemical Methods - Bushnell, Eric A. C.; Llano, Jorge; Eriksson, Leif A.; Gauld, James W. (IntechOpen, 2011)
None